Kapabilitas Pemerintah Desa Mengelola Aset Desa Dalam Menumbuhkan Kewirausahaan Sosial: (Studi Desa Gondowangi, Kecamatan Wagir, Kabupaten Malang, Jawa Timur - Nyimas Nadya Izana; Anik Susanti; Dano Purbo (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2019)
Government regulations in managing villages are basically aimed at building independence, various methods of assistance approaches have been implemented, none other than aiming at managing assets and organizing local residents. This has been stated in Law No. 6 of 2014 and No. 2 of 2018. Before Gondowangi village before the leadership of the current village head, the village experienced ups and downs which made the local community think of the village government as a structural government. However, it is different when the new village head changes. The village head can mobilize the community to develop the village potential that surrounds them including pamdes and waste management. From the success experienced by Desa Gondowangi, it made the writer to describe how the strategy of the village head of Gondowangi is currently in managing village assets in fostering social entrepreneurship. The research method used is descriptive qualitative. The results of the study indicate that the initial movement carried out by the village head was to make people aware of their village as an ancestral heritage. the field of public services has pamdes and waste management functions to minimize the risks of lack of drinking water and damage to river flow. At presentGondowangi Village has been able to independently turn on excellent public services and BUMDES with local insight.